(untitled) (Research, Society and Development, 2022)
This article, part of a broader master’s study on Chemistry Teaching in High School, aims to map academic productions on innovative didactic-pedagogical mediations. For that, as a methodology, we used the research called State of the Art, of bibliographic nature. We chose three specialized journals on the teaching of Chemistry, from 2017 to 2022: Revista da Sociedade Brasileira de Ensino de Química (ReSBEnQ), Revista Debates em Ensino de Química (REDEQUIM) and Revista Química Nova na Escola (QNEsc). The descriptors used for the search were: “Chemistry Teaching in Brazil”, “Mediations and Strategies in Chemistry Teaching” and “Learning in Chemistry Teaching”. After selecting the data produced, we reached a number of 145 publications in the three journals, of which, five articles in ReSBEnQ, sixty-three in REDEQUIM and seventy-seven publications in QNEsc. In this context, some final considerations can be pointed out: in addition to the innovative practices found, two caught our attention: those in which teachers manage to establish relationships between Chemistry and other areas of knowledge, apparently without affinities (literature, reading, art), to facilitate the conceptual understanding of chemical elements; on the other hand, the didactic-pedagogical experiences of Chemistry teachers aimed at students with special educational needs.